Fenomena Penyewaan Wi-Fi untuk Mencari Sumber Pembelajaran pada Anak Sekolah Dasar di Kampung Nangkasari 1 Pamijahan Bogor - rahmah, Nurul Fitriana; Mukri, Rusdiono; Hasanah, Tita (Prodi PGMI IAI Sahid, 2024)
This research explores the phenomenon of Wi-Fi rental for elementary school children. The purpose of this study is to understand the experiences of Wi-Fi renters, Wi-Fi service providers, and parents in assisting children's use of Wi-Fi rentals. The research method used is qualitative with a phenomenological approach. The research subjects consist of 4 Wi-Fi renter informants, 2 Wi-Fi service provider informants, 4 parent informants of Wi-Fi renters, and 1 key informant who is a village official (RT). Data collection techniques in this study include interviews, observations, and documentation. Data analysis is performed using the Triangulation technique. The research findings conclude three main points. First, children have various experiences in using this service, with positive effects such as ease in finding learning resources, but also potential risks associated with unsupervised internet usage. Second, Wi-Fi service providers face various challenges, ranging from children's requests to rate and rental schedule management. Third, parents play a crucial role in guiding children when using Wi-Fi, including supervision, wise usage, and managing internet usage time. The tendency toward permissive parenting is due to parents' lack of knowledge in operating gadgets and post-Covid-19 pandemic habits.